2008
DOI: 10.1021/ef800730f
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Oxidation over a Vanadia-based Selective Catalytic Reduction Catalyst

Abstract: The process of the reaction among elemental mercury (Hg 0 ) and reactive flue gas components across the selective catalytic reduction (SCR) catalyst was studied in a laboratory-scale reactor. Prepared vanadia-based SCR catalysts were characterized and analyzed to understand the potential reaction pathways. Mercury oxidation was observed when pro-exposure of the SCR catalyst to HCl, followed by passing through Hg 0 /N 2 in the absence of gas-phase HCl. At testing conditions, Hg 0 was found to desorb from the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 29 publications
8
104
0
Order By: Relevance
“…The strong coupling between NO reduction and Hg 0 oxidation via competitive adsorption of NH 3 and HCl was also independently validated with an extensive series of lab tests (Kamata et al, 2008). He et al (2009) observed HCl adsorption on monomeric vanadyl sites on a typical SCR catalyst, and suggested that such adsorbates explain the apparent inhibition of Hg 0 oxidation in the presence of NH 3 .…”
Section: Scr Unit Simulationsmentioning
confidence: 75%
“…The strong coupling between NO reduction and Hg 0 oxidation via competitive adsorption of NH 3 and HCl was also independently validated with an extensive series of lab tests (Kamata et al, 2008). He et al (2009) observed HCl adsorption on monomeric vanadyl sites on a typical SCR catalyst, and suggested that such adsorbates explain the apparent inhibition of Hg 0 oxidation in the presence of NH 3 .…”
Section: Scr Unit Simulationsmentioning
confidence: 75%
“…Hg el adsorption on the SCR catalyst surface was only observed in the absence of HCl [76,77]. When HCl or NH 3 was added to the simulated flue gas, a rapid mercury desorption was observed [23,76,77]. Eswaran and Stenger [76] also reported strong Hg adsorption in the presence of H 2 SO 4 .…”
Section: Mercury Adsorption On Scr-catalystsmentioning
confidence: 98%
“…Evidence of HCl adsorption on the catalyst surface was obtained by employing different surface analysis methods [23][24][25]. Following the reaction between HCl and the V 2 O 5 active sites on the catalyst surface, several vanadyl oxychloride complexes such as VOCl 2 , V 2 O 3 (OH) 2 Cl 2 , VO 2 Cl 2 are formed [23,24].…”
Section: Eley-rideal Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…(6)). Previous studies have indicated inorganic metal oxides in fly ash have significant mercury oxidation capacity [16,17]. And the sorbent itself can be oxidized with the occurrence of oxygen in flue gas (eq.…”
Section: Interaction Mechanism Of Fly Ash and Mercurymentioning
confidence: 99%